Insights on diet dynamics of Indian mackerel Rastrelliger kanagurta (Cuvier, 1816) - Upendra, Ganga; Radhakrishnan, C. K. (Indian Journal of Fisheries, 2020)
The diet of Indian mackerel Rastrelliger kanagurta (Cuvier, 1816) is reported based on the gut content analysis of specimens collected along the central Kerala coast, India. The study indicated ontogenetic variations in diet with diet breadth being highest in the largest size class of >231 mm total length (TL). Copepods followed by diatoms were the preferred food items. Detritus was an important diet component, especially during the pre-monsoon season and in the larger (>231 mm TL) size groups. The Preponderal Index (Ip) indicated seasonal differences in proportions of the various prey consumed. Spearman Rank Correlation Coefficient indicated similar diet quality during monsoon (June-September) and post-monsoon (October-January) seasons; but significant differences as compared to pre-monsoon season (February-May). Based on the results of the study, Indian mackerel was classified as an opportunistic feeder with a diet component that broadly reflects its seasonal-spatial habitats and local food availability. Keywords: Diet breadth, Diet seasonality, Indian mackerel, Ontogeny, Rastrelliger kanagurta